Estudo aplicativo de critérios e indicadores para avaliar sustentabilidade em uma empresa florestal em Tailândia, Pará, na Amazônia brasileira - Pokorny, B.; Bauch, R. (Empresa Brasileira de Pesquisa Agropecuária, 2000)
Application of Criteria and Indicators to assess the sustainability of a forest Enterprise in Tailândia, Pará in the Brazilian Amazon: Initial aim of the presented study was to contribute to the development of monitoring and auditing instruments for forest enterprises in the Brazilian Amazon, basing on criteria and indicators to assess sustainability (C&I). The study based on the assumption, that the practicability and viability of C&I depended on the consideration of interest, visions and values of forest stakeholders. The principal idea of the study was to identify differences between four different stakeholder groups (local actors, local government, local manager and researcher) in the evaluation of a set of C&I defined by international researchers during a workshop. These differences would be used as starting points to work out a common list of C&I suitable for monitoring and auditing. One important methodological element was the assessment of the sustainability of a Brazilian timber enterprise by practical application of C&I. The study confirmed the great potential of C&I as tools to assess the sustainability of timber enterprise activities and showed interesting differences between the evaluation of the C&I by the different stakeholder groups. It was clear that for the potential users of C&I monitoring and auditing tools, practicability and simplicity were very important as well as the relation of costs and benefits. The assessment methods had a strong influence on the results of evaluation. To facilitate the application of C&I in monitoring and auditing instruments, future efforts should concentrate on the definition of clearly defined verifiers and assessment methods, as well as the definition of specific recommendation indicated by the evaluation results.